SOSIALISASI DAMPAK PENCEMARAN PLASTIK TERHADAP BIOTA LAUT KEPADA MASYARAKAT DI PANTAI LHOK BUBON ACEH BARAT - Hayatun Nufus; Zuriat Zuriat (Jurnal Marine Kreatif, 2019)
At present, the use of plastic is a general consumption in modern society, most of the consumption of plastic is only used once. As a result, a pile of plastic waste will pollute the environment and eventually the plastic waste will end up at sea. The high percentage of plastic waste contamination in the sea as one of the contaminants that can have a negative impact, not only on the environment, but can have an impact on biota that exist in that environment. The method of carrying out community service activities includes the socialization of the impact of plastic waste pollution on biota as well as techniques to minimize excessive use of plastic waste in daily life. The results achieved in the implementation of community service activities are an increase in knowledge and care for the environment.